The Molecular Chaperone TCP1 Affects Carcinogenicity and Is a Potential Therapeutic Target for Acute Myeloid Leukemia - Yong Wu; Guihui Tu; Yuxia Yuan; Jingwen Liu; Qingna Jiang; Yang Liu; Qiurong Wu; Lixian Wu; Yuanzhong Chen (Pharmaceutics)
Background/Objectives: Acute myeloid leukemia (AML) is an aggressive malignancy marked by high relapse rates and molecular heterogeneity, necessitating the identification of novel therapeutic targets. T-complex protein 1 (TCP1), a chaperonin implicated in protein folding, remains underexplored in AML pathogenesis. This study investigates the functional role of TCP1 in AML progression and evaluates its therapeutic potential. Methods: Using successive generations of xenografted tumor models, we systematically assessed the correlation between TCP1 expression and AML tumorigenicity. Functional consequences of TCP1 silence were evaluated through in vitro proliferation assays and in vivo tumor growth monitoring. Two distinct inhibitory strategies were employed: miR-340-5p-mediated transcriptional silencing and FTY720-induced disruption of TCP1 chaperone activity. Mechanistic insights were derived from ubiquitin–proteasome pathway analysis, cell cycle profiling, and apoptosis assays. Results: High TCP1 expression correlated strongly with enhanced AML tumorigenicity. Knockdown of TCP1 significantly inhibited AML cell growth and induced degradation of AML1-ETO and PLK1 proteins through the ubiquitin–proteasome pathway. miR-340-5p effectively silenced TCP1 expression, exhibiting an inverse correlation with TCP1 levels. FTY720 disrupted TCP1′s chaperone function, leading to cell cycle arrest, apoptosis, and reduced xenograft tumor growth in murine models. Conclusion: Our findings establish TCP1 as a promising therapeutic target for AML. Both miR-340-5p and FTY720 demonstrate potent anti-leukemic effects by suppressing TCP1 activity, highlighting their potential as novel strategies to inhibit AML proliferation and improve therapeutic outcomes.